Tingkat Kepuasan Pasien Rawat Jalan Terhadap Pelayanan Kefarmasian Di Instalasi Farmasi Rumah Sakit Ibu dan Anak Di Kota Kupang Tahun 2015 - Ni Nyoman Yuliani; Jefrin Sambara; Hermanus Isman (JURNAL INFO KESEHATAN, 2017)
Patient satisfaction is a target that is often applied by comparing the results of health services received in hopes. Patients will feel satisfied if the service performance that they obtain is the same or exceeds their expectations and on the contrary, the patient will feel disappointed or dissatisfied if the health services obtained are not in line with their expectations. The purpose of this study was to measure the level of patient satisfaction with pharmaceutical services using five dimensions of service quality, namely reliability, responsiveness, confidence, appearance, and Empathy. This type of research is descriptive research. The sampling method was purposive sampling with criteria for reading and writing and being able to communicate well, with a minimum age characteristic of 17 years and over and had visited at least twice to visit the Mother and Child Hospital Pharmacy Installation in Kupang City. The results of these five (5) indicator dimensions state patient satisfaction at a hospital. This research was conducted by filling out questionnaires by patients and then calculating the percentage of patients' satisfaction window on the indicators under study. Based on the calculation of patient satisfaction level on reliability indicators of 88.22%, responsiveness indicators were 88.33%, confidence indicators were 86.39%, performance indicators were 87.63%, and empathy indicators were 88.45%.